2006
DOI: 10.1097/01.mlg.0000225936.88411.71
|View full text |Cite
|
Sign up to set email alerts
|

Management of Contralateral N0 Neck in Pyriform Sinus Carcinoma

Abstract: The patients with pyriform sinus SCC with clinically ipsilateral N+ neck and/or extension across the midline are at greater risk for contralateral occult neck metastases. Furthermore, patients who present with a contralateral metastatic neck have a worse prognosis than those staged as N0. Therefore, we advocate bilateral neck treatment in patients with pyriform sinus SCC with clinically ipsilateral node metastases and/or extension across the midline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 14 publications
1
33
0
2
Order By: Relevance
“…Koo et al reported that oral cavity cancer in advanced T stage has a high chance of contralateral occult nodal metastasis [6]. Also they reported in another study that hypopharynx cancer with clinically ipsilateral node positive and/ or extension across the midline is at greater risk for contralateral occult neck metastases [7]. However, the occult metastasis rate in this study was 7.5% (6 of 80 electively dissected necks, Table IV).…”
Section: Discussionmentioning
confidence: 78%
“…Koo et al reported that oral cavity cancer in advanced T stage has a high chance of contralateral occult nodal metastasis [6]. Also they reported in another study that hypopharynx cancer with clinically ipsilateral node positive and/ or extension across the midline is at greater risk for contralateral occult neck metastases [7]. However, the occult metastasis rate in this study was 7.5% (6 of 80 electively dissected necks, Table IV).…”
Section: Discussionmentioning
confidence: 78%
“…Data from multiple pathological studies [35][36][37][38][39][40] showed that metastases form clinically N0 hypopharyngeal cancer rarely occur in levels I and IIB, and they supported the recommendation to preserve levels I and IIB in these patients, which may improve the post-operative functional outcome, particularly with regard to the spinal accessory nerve and future shoulder function [41]. Contralateral nodal clearance may also be considered in the at-risked group of patients, including those with tumor involving the medial wall of the pyriform recess [42][43][44][45], post-crioid region or the posterior wall [43,[46][47][48], and those with ipsilateral palpable nodal metastasis and clinical stage IV disease.…”
Section: Management Of the Neckmentioning
confidence: 99%
“…HPC also has a high risk of contralateral lymph node metastasis due to the rich network of lymphatic anastomoses in the posterior pharyngeal wall [10] . In this study, bilateral cervical metastases appeared on days 14, 21, and 28, but the metastasis rate to the contralateral neck was higher than that of human HPC.…”
Section: Discussionmentioning
confidence: 99%